Surgical Management of Malunited Zygomaticomaxillary Complex Fracture: A Case Report - Chauhan, Vivek; Chaudhary, Gaurav; Tandon, Sapna; Chauhan, Himanshu; Tripathi, Anjali; Baruah, Pranami (Journal of Neonatal Surgery, 2025)
Introduction: The zygomaticomaxillary complex (ZMC) is a critical structural component of the midface, contributing to both facial aesthetics and function, particularly in maintaining orbital integrity. Fractures of the ZMC are common in high-impact trauma, such as road traffic accidents, and can lead to significant cosmetic and functional deficits if not managed appropriately. Case Presentation: An 18-year-old male presented to the Department of Oral and Maxillofacial Surgery with complaints of facial asymmetry and restricted mouth opening following a road traffic accident 20 days prior. Clinical and radiographic examination revealed a frontozygomatic suture fracture, infraorbital rim fracture, and malunion of the zygomatic arch. Surgical correction was carried out using a lateral brow incision, intraoral vestibular approach, and a stab incision over the arch. The malunited segments were re-fractured, anatomically reduced, and fixed with titanium miniplates. Discussion: Accurate diagnosis, surgical planning, and proper access to fracture sites are crucial for optimal results in ZMC fracture management. Literature supports multi-point fixation and emphasizes minimal scarring with intraoral approaches. Surgical expertise and tailored treatment plans significantly influence functional and aesthetic outcomes. Conclusion: Timely intervention with appropriate surgical techniques can effectively restore facial symmetry and function in ZMC fractures. Rigid fixation using miniplates and strategic incisions offers a reliable approach to managing complex malunited midfacial injuries.